Obstacles facing the application of the law of protection from abuse, from the point of view of workers in the Social Protection Department in Makkah Al-Mukarramah Region - Almalki, Fahad Ahmad Apopakr (Arab Journal for Sciences and Research Publishing, 2020)
The aim of the research is to uncover the obstacles facing the application of the law of protection from abuse, in the face of domestic violence, from the workers’ point of view, using the case study approach. For collecting data, the study relied on the interview and simple observation tool. The research community consists of specialized workers in the three cities during the study period, as their number reached (41) employees. The most important results were an increase in the volume of reports of domestic violence and a steady increase, with the total number during the three years (2107, 2018, and 2019), respectively (4748, 25375, and 33085). The results showed that the Social Protection Unit in the three cities plays a good role in handling reports of domestic violence and dealing with them. It also showed the weakness of the work environment in all its details, in terms of offices, devices, electronic system and means of communication, the lack of transportation, the absence of a shelter in Makkah Al-Mukarramah and the need for many cases to enter the home and the difficulty of accepting cases in other regions. The lack of a cadre of social workers, psychologists and administrators, the lack of financial incentives, the lack of a cadre of social workers on par with the psychologists, the poor knowledge of some employees about the role of social protection, the absence of a task guide for the employees, the lack of specialized training courses, as well as the new psychological measures, the female employees assigned to the role observers inside the home are not qualified to deal with cases of protection and social work, the weak role of the authorities in cooperation with social protection, and the lack of awareness of the importance of their work, and the weak response of the police. In light of these results, a number of recommendations were developed to reduce these obstacles.